2019
DOI: 10.24843/ejmunud.2019.v08.i11.p25
|View full text |Cite
|
Sign up to set email alerts
|

Peran Komitmen Organisasional Memediasi Pengaruh Kepemimpinan Transformasional Terhadap Ocb

Abstract: Tujuan penelitian ini adalah untuk mengetahui pengaruh kepemimpinan transformasional terhadap komitmen organisasional, untuk mengetahui pengaruh kepemimpinan transformasional terhadap OCB , untuk mengetahui pengaruh komitmen organisasional terhadap OCB , serta untuk mengetahui peran komitmen organisasional dalam memediasi pengaruh kepemimpinan transformasional terhadap OCB . Penelitian ini dilakukan pada Dinas Koperasidan UKM Provinsi Bali. Jumlah sampel yang digunakan dalam penelitian ini yaitu 56 orang, deng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The better the transformational leadership style is applied to a SME leader, the more committed the employee is to the organization (Pratama & Mujiati, 2019); (Perawati & Badera, 2018). At Dinas Koperasi dan UKM Provinsi Bali, transformational leadership improves organizational commitment (Pratama & Mujiati, 2019). We suggest the following first hypothesis based on the prior explanation.…”
Section: The Effect Of Transformational Leadership On Organizational ...mentioning
confidence: 92%
See 1 more Smart Citation
“…The better the transformational leadership style is applied to a SME leader, the more committed the employee is to the organization (Pratama & Mujiati, 2019); (Perawati & Badera, 2018). At Dinas Koperasi dan UKM Provinsi Bali, transformational leadership improves organizational commitment (Pratama & Mujiati, 2019). We suggest the following first hypothesis based on the prior explanation.…”
Section: The Effect Of Transformational Leadership On Organizational ...mentioning
confidence: 92%
“…Several prior research have found a link between transformational leadership and organizational commitment (G. W. Allen et al, 2017); (Pratama et al, 2020). The better the transformational leadership style is applied to a SME leader, the more committed the employee is to the organization (Pratama & Mujiati, 2019); (Perawati & Badera, 2018). At Dinas Koperasi dan UKM Provinsi Bali, transformational leadership improves organizational commitment (Pratama & Mujiati, 2019).…”
Section: The Effect Of Transformational Leadership On Organizational ...mentioning
confidence: 99%